The Book Collection of John Ostewyk, Chaplain of St Magnus the Martyr, London, 1495 - Payne, M T W (Library, 2024)
Abstract This note offers a transcription, and brief discussion, of the probate inventory of John Ostewyk, a priest in the parish of St Magnus the Martyr in London, who died in 1495. Among his belongings, the appraisers found seventeen named volumes and twenty pamphlets. These are additional to books mentioned in his will. Some of the volumes can be identified with surviving editions.